The Influence of Beauty Influencer Credibility, Live Streaming, and Advertisements on Make Over Purchasing Decisions on the TikTok Application in Surabaya City - Devitasari, Shinta; Ugy Soebiantoro (Jurnal Economic Resource, 2025)
The development of digital technology encourages local cosmetic brands, such as Make Over, by utilizing the Tiktok social media platform as a marketing medium. This study aims to analyze the effect of beauty influencer credibility, live streaming, and advertising on Make Over purchasing decisions on the Tiktok application in Surabaya City. The population in this study were Make Over consumers who placed orders through the Tiktok application in Surabaya City, with a sample size of 104 respondents. This study uses a quantitative approach with purposive sampling technique. The analysis technique used is Partial Least Square (PLS) with SmartPLS 3.0. The results of this study indicate that the three independent variables, namely beauty influencer credibility, live streaming, and advertising have a positive and significant effect on purchasing decisions. These findings indicate that interaction and trust-based digital marketing strategies such as those offered by beauty influencers, live streaming, and advertising can increase consumer buying interest in social media platforms.